(untitled) (Bombay Hospital Journal, 2021)
“Papa, all is well, I am settled in my new hostel and I am going to join my Neurology unit today, wish me luck!” Aditya made an early morning call as he was getting ready to join the new Neurology posting. Of course, his parents were delighted, and he had struggled so much to get admission to this prestigious course. Neurologists are so few in the country, only a few thousand for such a large population, and their son was entering such a respected specialty of medicine. The “brain doctor” holds a special place in the rank and file of medical professionals as he deals with the most complicated and perhaps most evolved organ in the human body